Efektivitas Pemahaman Standar Akuntansi Sektor Publik terhadap Proses Penyusunan Laporan Keuangan pada Badan Pengelolaan Keuangan Aset Daerah Kabupaten XYZ - Wibisono, khairunnisa Arif Fajar; Wibisono, Arif Fajar (Masyarakat Ekonomi Syariah Bogor, 2024)
The Regional Financial and Asset Management Body (BPKAD) is a regional apparatus that has an important role in managing regional finances as well as creating and realizing accurate and reliable financial reports. This research aims to determine the presenters' understanding of public sector accounting standards in BPKAD district xyz in the process of preparing financial reporting. Encourage the realization of accountability to be responsible to society by reporting finances according to government accounting standards. Consistency in implementing government accounting standards is needed to improve the quality of regional government financial reports (LKPD). This research uses a qualitative approach with a case study method. The results of the research show that the understanding of financial report presenters at BPKAD The recommendations given are the need to increase human resource competency, strengthen coordination between OPDs, and provide more opportunities for staff with expertise or accounting backgrounds to join the agency.